A COMPETITIVENESS AND INNOVATIVENESS IN THE ATTRACTIVENESS OF A TOURIST DESTINATION : Case Study - Tourist Destination Oltenia - Dragomir, Loredana; Mazilu, Mirela; Marinescu, Roxana; Bălă, Dumitru (Advances in Social Sciences Research Journal, 2019)
Competitiveness together with innovation are printed on all components of a tourist destination, from the tourist product to the elements of attraction, infrastructure, entertainment, human resources, image and character, not forgetting the price that can launch or restrict it on a dynamic tourist market where quality overtakes in recent years and meets dynamic tourist demand. This article aims to analyze the two imperative components in the sustainable functionality of a tourist destination, inseparable binomial, competitiveness and innovation as the only viable ways of halting the decline in the lifecycle of a tourist destination Oltenia. The article also attempts to apply for the Oltenia region the criteria for denominate a tourist destination in the optics of regional competitiveness and more, a tourist destination which is unfortunately currently not competitive, although it has the necessary parameters for identifying competitiveness (natural and cultural resources, customs and traditions, unique local products, tourist identity, etc.). Through specific geographical methods (diagnosis, prospective, documentary, graphical representation, and also Butler's TALC model) the article sets out a complex theoretical and methodological framework, with factual determinations in promoting the destination Oltenia as a destination of excellence in Romania (The Danube Gorge may be considered as the region's visiting card, being thus awarded the title of "European Destination of Excellence" in 2008).